S-53-6: ANALYSIS OF BP SCREENING IN PAKISTAN (MMM EXPERIENCE). (January 2023) - Ishaq, Mohammad
Abstract : Pakistan Hypertension League, under the banner of MMM, conducted a cross-sectional survey by involving all of its 14 regional chapters, throughout Pakistan. More than 150 volunteers were selected to conduct this survey with the help of pharmaceutical industry and were trained at PHL regional chapters. Screening camps were arranged in the month of May, at public places, hospitals and various institutions to allow general public to be screened for their BPs after taking their informed consent. MMM pre piloted data tool was used to record the demographic data including age and gender. Blood pressure of every individual was recorded in sitting position by using an OMRON digital BP apparatus. A subject was classified as having hypertension if the BP reading of >140/90mmHg or in those taking medication for high BP. All data were coded and analyzed by the MMM statistics team. We present the screening results from three consecutive years (2017, 18, 19).A total of 37328 individuals screened of which 21270 (66.32%) were male and 16058 (33.8%) females. Mean age was 45.1 years. Mean systolic and diastolic B.P were 128.7 by 82.7 mmHg. A total of 21270 (55.3%) were found to be hypertensive. Further analysis of largest data from 2018, screened 25076, out of which 14726 (58.7%) were hypertensive. Out of them 11681 (79.3%) were aware and 10759 (73.1%) were taking antihypertensives. Only 47.3% of those on medications had controlled BP, while only 34.5% of screened had their BP controlled less than or equal to 140/90 mmHg. Those who never had their BP checked were 26.3%. Diabetes Mellites was the commonest co-morbidity 29.2%, followed by previous MI and Stroke 12.9% and 12.4% respectively. In summary the prevalence of High BP in Pakistan was very high compared to other countries in the region. This data for logistic purposes belongs to urban & semi urban population. More surveys are required including rural communities.